Liturgical Spirituality and Ethical Formation: The Formulary of St John de Matha - Santos, Marvin Jhan (The way, 2025)
The article explores the liturgical spirituality and ethical formation exemplified in the Formulary of St John de Matha, highlighting how the Order of the Most Holy Trinity, founded by John de Matha (1160-1213), integrates worship, charitable action, and social responsibility. It discusses how liturgy functions as a formative practice that shapes Christian moral identity, linking ritual participation and Eucharistic worship to ethical engagement, and social justice.